Protective Effect Conferred by Isometric Preconditioning Against Slow- and Fast-Velocity Eccentric Exercise-Induced Muscle Damage - Barreto, Renan Vieira; de Lima, Leonardo Coelho Rabello; Greco, Camila Coelho; Denadai, Benedito Sérgio (Frontiers in Physiology, 2019)
We investigated if the same isometric preconditioning protocol (IPP) attenuates the magnitude of muscle damage induced by different maximal eccentric exercise protocols in the elbow flexors. Sixty-four untrained men were assigned to either two experimental or two control groups. Participants in the experimental groups performed an IPP prior to either slow (60°·s-1 – ISO+ECC-S) or fast (180°·s-1 – ISO+ECC-F) maximal eccentric contractions (MaxECC). Subjects in the control groups performed slow (ECC-S) or fast (ECC-F) MaxECC without IPP. Maximal isokinetic concentric torque (MVC), muscle soreness (SOR) and muscle thickness (MT) were assessed before, immediately after, and 1-4 days following the MaxECC. Significant (p < 0.05) group vs time interactions were found for MVC (F = 4,517), SOR (F = 6,318), and MT (F = 1,863). The ECC-S group presented faster (p<0.05) recovery of MVC and MT and less (p<0.05) SOR at 96h post-MaxECC compared with ECC-F group. No significant differences in MVC and MT were found between ECC-S and ECC-F groups following MaxECC. The ISO+ECC-S group showed faster (p<0.05) recovery of MVC and SOR compared to the ECC-S group. No significant differences were evident between ISO+ECC-S and ECC-S in any variable. The ISO+ECC-F group showed faster (p<0.05) recovery of all assessed variables compared with the ECC-F group. MVC was greater (p<0.05) at 48-72h and SOR was less (p<0.05) at 48-96h in the ISO+ECC-F compared to the ECC-F group. No significant differences were evident between ISO+ECC-S and ISO+ECC-F for any variable. These results show that the IPP accelerated recovery of MVC and SOR for the slow-eccentric exercise condition and attenuated strength loss and SOR in addition to faster recovery of all assessed variables for the fast-eccentric exercise condition. Therefore, the IPP can be used as a strategy to attenuate and accelerate recovery of muscle damage induced by different-velocity eccentric exercises, resulting in greater protection against muscle damage induced by faster velocity.